Faktor yang Berhubungan dengan Stres pada Ibu Hamil selama Pandemi di Wilayah Kerja Puskesmas Bandar Jaya Kabupaten Lampung Tengah - Aan Nurhasanah; Aryanti Wardiyah; Rilyani Rilyani (Malahayati Nursing Journal, 2023)
ABSTRACT Coronavirus disease 2019 (covid-19) is a severe acute respiratory virus. The covid-19 pandemic is a contributing factor to stress for pregnant women because pregnant women and their fetuses are at high risk of spreading Covid-19 in the community. Including the concerns of pregnant women to make a pregnancy check-up visit. To find out the stress level of pregnant women facing childbirth during the covid-19 pandemic in the work area of the Bandar Jaya Health Center in 2022. The type of research used is quantitative. The research design used is cross sectional. The population of this study was all pregnant women in the working area of the Bandar Jaya Health Center from January to December 2021. The sample of this study amounted to 161 pregnant women. In this study, research measuring instruments were used in the form of a respondent characteristic questionnaire and a DASS stress questionnaire. This study uses univariate, bivariate, and multivariate data analysis. Based on frequency data, the average age of the respondents is 30 years, the majority of gestational age is in the third trimester, the most education is high school education 69.6%, the majority work as IRT, the average parity is 2, the highest ethnicity is Javanese. The results of the multiple correlation test obtained a correlation coefficient of 0.567 and the results of multiple linear regression at gestational age were found to be p value 0,000 0,05. There is a relationship between the respondent's age, gestational age, education and parity with the stress of pregnant women in facing childbirth during the Covid-19 pandemic with a strong correlation. The most influential variable with the stress of pregnant women is gestational age. While the variables that have no effect on stress during the Covid-19 pandemic include work and ethnicity. The majority of pregnant women have stress with an average value of 21, where the value of 21 is classified as moderate stress and the percentage of moderate stress is 46.6%. Keywords: Stress, Pregnant Women, Covid-19  ABSTRAK Penyakit Coronavirus 2019 (covid-19) adalah virus pernapasan akut yang parah. Pandemi covid-19 adalah faktor yang berkontribusi terhadap stres pada ibu hamil karena ibu hamil dan janinnya berisiko tinggi penyebaran Covid-19 di masyarakat. Termasuk dengan kekhawatiran ibu hamil untuk melakukan kunjungan periksa kehamilan.  Diketahui faktor yang berhubungan dengan stres ibu hamil dalam menghadapi persalinan di masa pandemi covid-19 di wilayah kerja Puskesmas Bandar Jaya Kabupaten Lampung Tengah Tahun 2022. Jenis penelitian yang digunakan adalah kuantitatif. Dengan desain penelitian yang digunakan adalah cross sectional. Populasi penelitian ini adalah seluruh ibu hamil di wilayah kerja Puskesmas Bandar Jaya dari bulan Januari hingga Desember tahun 2021. Sampel penelitian ini berjumlah 161 ibu hamil. Alat ukur penelitian berupa kuesioner karakteristik responden dan kuesioner stres DASS-42. Penelitian ini menggunakan analisis data univariat, bivariat dan multivariat.Berdasarkan data karakteristik responden didapatkan rata-rata usia responden 30 tahun, usia kehamilan mayoritas di trimester ketiga, pendidikan terbanyak adalah pendidikan SMA 69,6%, pekerjaan mayoritas sebagai IRT, rata-rata paritas adalah 2, dan suku terbanyak adalah suku jawa. Hasil uji korelasi berganda didapatkan koefisien korelasi 0.567 dan hasil regresi linier ganda pada usia kehamilan diketahui p value 0,000 0,05. Terdapat hubungan antara usia responden, usia kehamilan, pendidikan dan paritas dengan stres ibu hamil dengan korelasi yang kuat. Variabel yang paling berpengaruh dengan stres ibu hamil adalah usia kehamilan. Sedangkan variabel yang tidak ada pengaruh terhadap stres selama masa pandemi covid-19 diantara nya yaitu pekerjaan dan suku. Mayoritas ibu hamil memiliki stres dengan nilai rata-rata 21, dimana nilai 21 tergolong kedalam stres sedang dan untuk persentase stres sedang yaitu sebesar 46,6%. Kata Kunci: Stres, Ibu Hamil, Covid-19